Why and how EFL students learn vocabulary in parliamentary debate class - Aclan, Eunice M.; Abdul Aziz, Noor Hashima (Australian International Academic Centre, Australia, 2015)
Vocabulary, the backbone of any language including English, is foundational for listening, speaking, reading and writing.These four macro-skills are necessary not only in gaining knowledge as English is the language to access major information sources particularly the World Wide Web but also in the demanding globalized workplace.Vocabulary is seen to be learned better when it is contextualized thus language teachers should design communicative activities such as debate. However, debate, being more known as a competitive rather than a classroom activity worldwide, has not been explored yet for its potential to develop vocabulary among EFL/ESL students although it has been identified for its power in developing communication skills in general as well as critical thinking and other soft skills.Thus, this qualitative study was conducted to explore why and how EFL students learn vocabulary in classroom debate.The data were gathered through end-of-course evaluation and focus group interview with seven participants from the Middle East, African and ASEAN countries.The findings show that students learned vocabulary due to debate’s interactive nature requiring contextualized and meaningful language use from preparation to actual debate. EFL students described how they learned vocabulary through debate which has implications for SLA and language teaching.